Structure and absolute configuration of diterpenoids from hymenaea stigonocarpa - Monteiro, Afif F.; Batista, Joao M. [UNESP]; Machado, Michelle A.; Severino, Richele P.; Blanch, Ewan W.; Bolzani, Vanderlan da Silva [UNESP]; Vieira, Paulo C.; Severino, Vanessa G. P. (Amer Chemical Soc, 2015)
Chemical investigations of the ethanolic extracts from the flowers and leaves of Hymenaea stigonocarpa Mart. ex Hayne afforded one new ent-halimane diterpenoid, 18-hydroxy-ent-halima-1(10),13-(E)-dien-15-oic acid (1), together with five known compounds (2-6). The structural elucidation was performed by means of NMR (COSY, HSQC, HMBC, and NOESY) and MS analyses. Complete ¹H and ¹³C NMR data assignments are also reported for labd-13-en-8 beta-ol-15-oic (2) and labd-7,13-dien-15-oic (3) acids. The absolute configurations of 1 and 2 were established by comparison of experimental and calculated Raman optical activity spectra.